Optimizing of TiO2 Separation from Bangka Ilmenite by Leaching Process Using HCl - Sayekti Wahyuningsih; Hari Hidayatullah; Edi Pramono (ALCHEMY Jurnal Penelitian Kimia, 2014)
Separation of titanium dioxide (TiO2) from ilmenite Bangka has been done byleaching processusing HCl. Before the leaching process, ilmenite was roastedat 900oC for pre-oxidation (preliminary - oxidation). Leaching process carried out by variation of HCl concentration and Fe0 reducing agents. While the re-deposition of dissolved Ti4+ ion achieved by hydrolysis - condensation using 2-propanol-H2O solvents. Leaching the pre-oxidazed ilmenite shows the phase change of  pseudobrokite (Fe2TiO5) into hematite (Fe2O3) and synthetic rutile (TiO2). Formation of the synthetic rutile was characterized by the loss of intensity of Fe2TiO5 at 26.65º and the increasing intensity of rutile TiO2 at 27.49º.The dissolution rate of both titanium and iron was found to be increased, generally, by increasing acid concentration in case of HCl as well as by increasing ilmenite: Fe0 ratio. Precipitation of the dissolved titania with 2-propanol -H2Oof 8:2(v /v) produced anatase TiO2 due to the hydrolysis and condensation of Ti-tetra isopropoxide complexes.